Genetic differences and population structure of Capsicum spp. populations with simple sequences repets markers (SSRs) (Bioagro, 2024)
In the Solanaceae family, Capsicum spp. is a worldwide important vegetable genus, and widely cultivated in Mexico. The objective of this research was to know the genetic relation, genetic diversity, and genetic structure of fourteen populations of Capsicum spp. (six from Tabasco, five from Tamaulipas, Mexico, and three from Cuba) the four oligonucleotides identified 202 alleles, 38 of them were polymorphics. The majority of alleles (65) were amplified by oligo HpmsCaSIG19 and Hpms1-274 detected a small amount of alleles (35), the average of alleles was 50,5. The genetic structure of the population was estimated with the F fixation indices. The value of the diversity between regions (PhiRT) was 0,264, this means that the populations presented 73,6% of variation between them. High diversity was found between subpopulations and inside regions (PhiPR=0,412). The PhiPT (analog of FST)=0,567, can be interpreted as high differentiation in the genics frequency of the populations that were evaluated. The cluster analysis classified the fourteen populations at a distance of 11 in five groups, the clusters I and III were formed by four populations on each one, while, two populations per cluster were observed in the clusters II, IV, and V. In this analysis, the population Cachucha of Cuba was not related with the backcrosses Habanero x Amashito (RCHaAm) and Garbanzo x Habanero (RCGaHa), also was not related with the Habanero population of Tabasco Mexico.
Keywords: Capsicum spp.; chili populations; genetic diversity; phylogenetic relations; SSR markers